Notes on three raptor species new to Flores - Jan Verhoeye; Ben King (KUKILA, 1990)
Details are given of sightings of Bonelli's Eagle Hieraaetus fasciatus. Rufous-bellied Eagle H. kienerii and a Honey-Buzzard Pernis sp. on Flores, extending the known range of these species